Keeping a legacy alive: His elder brother's death was a cruel blow but Aril Pilus vows to fulfil Izwan's wishes - Chua, Dennis (New Straits Times, 2012)
BUBBLY and cheerful Khairil Azam "Aril" Pilus' life was shattered when his elder brother and soul mate Izwan died after a long illness last February at only 33.